8z+6-4z=30-4z

Simple and best practice solution for 8z+6-4z=30-4z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8z+6-4z=30-4z equation:


Simplifying
8z + 6 + -4z = 30 + -4z

Reorder the terms:
6 + 8z + -4z = 30 + -4z

Combine like terms: 8z + -4z = 4z
6 + 4z = 30 + -4z

Solving
6 + 4z = 30 + -4z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '4z' to each side of the equation.
6 + 4z + 4z = 30 + -4z + 4z

Combine like terms: 4z + 4z = 8z
6 + 8z = 30 + -4z + 4z

Combine like terms: -4z + 4z = 0
6 + 8z = 30 + 0
6 + 8z = 30

Add '-6' to each side of the equation.
6 + -6 + 8z = 30 + -6

Combine like terms: 6 + -6 = 0
0 + 8z = 30 + -6
8z = 30 + -6

Combine like terms: 30 + -6 = 24
8z = 24

Divide each side by '8'.
z = 3

Simplifying
z = 3

See similar equations:

| 39x+3+8x=144 | | (26w^2)(52w)=9360 | | 8x-2(5-x)=11 | | (26w^2)x(52w)=9360 | | -(-4/3+3p)=19/3-5p | | 9x+4-2x=7x-6+x | | 26w^2+52w=9360 | | (y/3)+(y/4)=(5/6) | | (a/3)=333 | | -(4/3+3p)=19/3-5p | | -4=b-2 | | 3a+4=2a+5 | | (a*3)=333 | | 3x+11+2x+4x=75 | | r^2+2r-143=0 | | -5x+16=-44 | | (X+2)=5(x+4) | | 1.9+6.6n=-2.5n-3(-3n-0.6) | | -3.2x=-28.8 | | 2c-3=6c+25 | | -4(-1.6-8.2n)=11.4+33.8n | | -13+5=x+8 | | -4(1.6-8.2n)=11.4+33.8n | | 3+8+x=4+7 | | 4x+10+18x-10=120 | | 7n-(1+3n)=-8 | | -5x+4(-3+4x)=-10.8+10.6x | | x(x+0.3)=5.6 | | 81y-8x=-65 | | X+28+x+36=64 | | x^6-125y^9= | | 4x+1/x-1=20x-3/5x-7 |

Equations solver categories